Nano silicon dioxide aerogel glass fiber mat and preparation method thereof
Through the multi-layer composite structure and wetting agent treatment of nano-silicon dioxide aerogel glass fiber felt, the problem of insufficient noise reduction and thermal insulation performance of existing glass fiber felt was solved, and significant noise reduction and mechanical performance improvement were achieved. Suitable for a variety of composite occasions.
Patent Information
- Application Number
- CN202411381328.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing fiberglass felt lacks performance in an environment with noise reduction demand, and the production process has problems of high energy consumption and low investment.
Using nano-silica aerogel glass fiber felt, the glass fiber felt and nano-silica aerogel are laminated to form a multi-layer composite structure, and the binding force is improved by wetting agent treatment, and the thermal pressing curing and aging treatment are enhanced. performance.
It has achieved significant noise reduction, heat insulation, fire resistance and flame retardant and improved mechanical performance, and is suitable for a variety of composite occasions, especially in the electrical field as an insulating material.
Smart Images

Figure CN119239076A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass fiber felt, in particular to a nano silicon dioxide aerogel glass fiber felt and a preparation method thereof. Background Art
[0002] Glass fiber mat, as a thin sheet product made of continuous filaments or chopped filaments in an irrational manner through chemical binders or mechanical action, has become an indispensable and important material in modern industry due to its excellent performance and wide range of applications.
[0003] The production process of glass fiber mat mainly includes centrifugal blowing process and flame blowing process. The centrifugal blowing process evenly distributes the high-temperature molten glass liquid to the inner surface of the centrifuge, uses centrifugal force to form a uniform liquid film, and then solidifies and dries after drafting, separation and spraying of binder. The glass fiber produced by this process has a larger diameter, but has the characteristics of high energy consumption. The flame blowing process is relatively simple and requires less investment. It uses high-speed and high-temperature flame airflow to further melt and separate the primary glass fiber, prepare glass fibers with smaller diameters, and collect and solidify them into mats under the action of the jet airflow.
[0004] Glass fiber mat has a wide range of applications, including:
[0005] 1. Construction industry, 2. Automobile industry, 3. Shipbuilding industry, 4. Electrical industry, 5. Packaging industry.
[0006] With the continuous advancement of science and technology and people's increasing requirements for the performance of glass fiber felt, especially when used in environments with noise reduction requirements, higher performance requirements are put forward for glass fiber felt.
[0007] Therefore, the present invention solves the corresponding problems by providing nano-silica aerogel glass fiber mat. Summary of the invention
[0008] The purpose of the present invention is to provide a nano-silicon dioxide aerogel glass fiber mat to solve the deficiencies in the prior art.
[0009] The technical solution adopted by the present invention is as follows:
[0010] Nano-silica aerogel glass fiber mat, wherein the nano-silica aerogel glass fiber mat is obtained by treating the glass fiber mat with a sizing agent and then laminating it with nano-silica aerogel;
[0011] Among them, the mixing ratio of glass fiber mat and sizing agent is 1:10-12;
[0012] The nano-silicon dioxide aerogel layer is formed by coating nano-silicon dioxide aerogel on the surface of glass fiber mat and then curing it.
[0013] As a further technical solution: the thickness of the glass fiber felt layer is 0.2-0.3 mm; the thickness of the nano-silicon dioxide aerogel layer is 0.1-0.2 mm.
[0014] As a further technical solution: the preparation method of the infiltrant is:
[0015] Add deionized water and composite emulsifier into the reactor and stir and mix for 15 minutes;
[0016] Add methyl methacrylate and isooctyl acrylate into the reactor, adjust the temperature to 50°C, keep warm, and stir for 30 minutes;
[0017] Lauryl acrylate, sodium dodecyl sulfate, castor oil and deionized water were mixed in sequence and stirred at high speed for 10 minutes to obtain a composite liquid;
[0018] adding the initiator to water to prepare an initiator solution;
[0019] The initiator solution was added to the composite solution and stirred for 10 min to obtain a mixed solution;
[0020] The mixed solution was added dropwise into the reaction kettle at a volume ratio of 1:3, the temperature was adjusted to 80° C., the mixture was stirred for 4 hours, and then cooled to room temperature to obtain a wetting agent.
[0021] As a further technical solution: the composite emulsifier is a mixture of alkylphenol polyoxyethylene ether and sodium lauryl sulfate;
[0022] The mixing mass ratio of the alkylphenol polyoxyethylene ether and sodium lauryl sulfate is 3:1-1.2;
[0023] The mass ratio of the composite emulsifier to deionized water is 1:28.
[0024] As a further technical solution: the mixing mass ratio of methyl methacrylate and isooctyl acrylate is 2:1;
[0025] The mass ratio of methyl methacrylate to composite emulsifier is 42-45:1;
[0026] The mixing mass ratio of the lauryl acrylate, sodium lauryl sulfate, castor oil and deionized water is 10-14:1:3:30.
[0027] As a further technical solution: the mass fraction of the initiator solution is 3%;
[0028] The initiator is ammonium persulfate;
[0029] The mixing mass ratio of the initiator solution to the composite liquid is 1:40.
[0030] As a further technical solution: the preparation method of the nano-silicon dioxide aerogel is:
[0031] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 15 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0032] Among them, the stirring speed is 500r / min;
[0033] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 55:6:2;
[0034] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2;
[0035] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 40° C., the mixture was stirred for 2 hours, and then silica sol was added, and the mixture was stirred for 20 minutes to obtain.
[0036] As a further technical solution: the deionized water and methyltriethoxysilane are mixed in a mass ratio of 45:10;
[0037] The volume ratio of deionized water to silica sol is 10:1;
[0038] Among them, the heat preservation stirring speed is 250r / min.
[0039] As a further technical solution: the nano-silica aerogel glass fiber mat comprises at least 3 layers of glass fiber mat layers and at least 2 layers of nano-silica aerogel layers.
[0040] The preparation method of nano-silicon dioxide aerogel glass fiber felt comprises the following steps:
[0041] (1) Prepare the substrate: glass fiber mat;
[0042] (2) preparing nano-silicon dioxide aerogel;
[0043] (3) Coating:
[0044] The nano-silicon dioxide aerogel is uniformly coated on the surface of the glass fiber mat, and then covered with another layer of glass fiber mat, and then a layer of nano-silicon dioxide aerogel is repeatedly coated on the surface of the new glass fiber mat, and then covered with another layer of glass fiber mat to obtain a preliminary sample;
[0045] (4) Hot pressing curing:
[0046] The obtained preliminary sample was placed at a temperature of 60-65°C and hot pressed for 1 hour, wherein the hot pressing pressure was 0.12MPa;
[0047] (5) Aging:
[0048] After hot pressing, the product is aged for 3 days in an air atmosphere at 55°C.
[0049] Beneficial effects:
[0050] characteristic:
[0051] The nano-silica aerogel glass fiber mat prepared by the present invention is a composite of glass fiber mat and aerogel through a 3-layer and 2-layer structure. The formed composite structure not only has excellent thermal insulation performance, but also has excellent sound insulation and noise reduction performance. When applied to an environment requiring noise reduction, it can significantly reduce the noise volume. In addition, the nano-silica aerogel glass fiber mat prepared by the present invention also has excellent fire retardant performance.
[0052] The present invention greatly improves the binding force of the two by impregnating the glass fiber with an impregnant and then combining it with an aerogel layer. When sound waves invade the nano-silica aerogel glass fiber felt, the sound waves will produce friction and cyclic rebound effects with the fibers, pores, etc. inside the nano-silica aerogel glass fiber felt, so that a large amount of sound waves are absorbed, thereby achieving a significant noise reduction effect.
[0053] Since glass fiber felt is resistant to high temperatures, has good mechanical properties, and high chemical stability, it is an excellent insulating material. Therefore, the nano-silica aerogel glass fiber felt prepared by the present invention can be applied in the electrical field as an insulating material.
[0054] The nano-silica aerogel glass fiber mat prepared by the present invention adopts a multi-layer composite structure and contains fixed air pockets inside. It can better resist impact and vibration by relying on the ultra-high tensile strength of the glass fiber mat substrate and the excellent elasticity of the aerogel layer.
[0055] Compared with other materials, the nano silicon dioxide aerogel glass fiber felt prepared by the present invention has low density, light weight and soft texture, and can be applied to a variety of composite occasions. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is the structure diagram of nano-silica aerogel glass fiber mat;
[0057] Among them, 1 is a glass fiber felt layer, and 2 is a nano-silica aerogel layer. DETAILED DESCRIPTION
[0058] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] The following are specific embodiments
[0060] Example 1
[0061] Nano-silica aerogel glass fiber mat, wherein the nano-silica aerogel glass fiber mat is obtained by treating the glass fiber mat with a sizing agent and then laminating it with nano-silica aerogel;
[0062] Among them, the mixing ratio of glass fiber mat and sizing agent is 1:10;
[0063] The nano-silicon dioxide aerogel layer is formed by coating nano-silicon dioxide aerogel on the surface of glass fiber mat and then curing it.
[0064] The thickness of the glass fiber felt layer is 2 mm; the thickness of the nano-silica aerogel layer is 1 mm.
[0065] The preparation method of the infiltrant is:
[0066] Add deionized water and composite emulsifier into the reactor and stir and mix for 15 minutes;
[0067] Add methyl methacrylate and isooctyl acrylate into the reactor, adjust the temperature to 50°C, keep warm, and stir for 30 minutes;
[0068] Lauryl acrylate, sodium dodecyl sulfate, castor oil and deionized water were mixed in sequence and stirred at high speed for 10 minutes to obtain a composite liquid;
[0069] adding the initiator to water to prepare an initiator solution;
[0070] The initiator solution was added to the composite solution and stirred for 10 min to obtain a mixed solution;
[0071] The mixed solution was added dropwise into the reaction kettle at a volume ratio of 1:3, the temperature was adjusted to 80° C., the mixture was stirred for 4 hours, and then cooled to room temperature to obtain a wetting agent.
[0072] The composite emulsifier is a mixture of alkylphenol polyoxyethylene ether and sodium lauryl sulfate;
[0073] The mixing mass ratio of the alkylphenol polyoxyethylene ether and sodium lauryl sulfate is 3:1;
[0074] The mass ratio of the composite emulsifier to deionized water is 1:28.
[0075] The mixing mass ratio of methyl methacrylate and isooctyl acrylate is 2:1;
[0076] The mass ratio of methyl methacrylate to composite emulsifier is 42:1;
[0077] The mixing mass ratio of the lauryl acrylate, sodium lauryl sulfate, castor oil and deionized water is 10:1:3:30.
[0078] The mass fraction of the initiator solution is 3%;
[0079] The initiator is ammonium persulfate;
[0080] The mixing mass ratio of the initiator solution to the composite solution is 1:40.
[0081] The preparation method of nano-silica aerogel is as follows:
[0082] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 15 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0083] Among them, the stirring speed is 500r / min;
[0084] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 55:6:2;
[0085] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2;
[0086] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 40° C., the mixture was stirred for 2 hours, and then silica sol was added, and the mixture was stirred for 20 minutes to obtain.
[0087] The mass ratio of deionized water and methyltriethoxysilane is 45:10;
[0088] The volume ratio of deionized water to silica sol is 10:1;
[0089] Among them, the heat preservation stirring speed is 250r / min.
[0090] The nano-silica aerogel glass fiber mat comprises 3 layers of glass fiber mat and 2 layers of nano-silica aerogel.
[0091] The preparation method of nano-silicon dioxide aerogel glass fiber felt comprises the following steps:
[0092] (1) Prepare the substrate: glass fiber mat;
[0093] (2) preparing nano-silicon dioxide aerogel;
[0094] (3) Coating:
[0095] The nano-silicon dioxide aerogel is uniformly coated on the surface of the glass fiber mat, and then covered with another layer of glass fiber mat, and then a layer of nano-silicon dioxide aerogel is repeatedly coated on the surface of the new glass fiber mat, and then covered with another layer of glass fiber mat to obtain a preliminary sample;
[0096] (4) Hot pressing curing:
[0097] The obtained preliminary sample was placed at a temperature of 60°C and hot pressed for 1 hour, wherein the hot pressing pressure was 0.12MPa;
[0098] (5) Aging:
[0099] After hot pressing, the product is aged for 3 days in an air atmosphere at 55°C.
[0100] Example 2
[0101] Nano-silica aerogel glass fiber mat, wherein the nano-silica aerogel glass fiber mat is obtained by treating the glass fiber mat with a sizing agent and then laminating it with nano-silica aerogel;
[0102] Among them, the mixing ratio of glass fiber mat and sizing agent is 1:11;
[0103] The nano-silicon dioxide aerogel layer is formed by coating nano-silicon dioxide aerogel on the surface of glass fiber mat and then curing it.
[0104] The thickness of the glass fiber felt layer is 2 mm; the thickness of the nano-silica aerogel layer is 1 mm.
[0105] The preparation method of the infiltrant is:
[0106] Add deionized water and composite emulsifier into the reactor and stir and mix for 15 minutes;
[0107] Add methyl methacrylate and isooctyl acrylate into the reactor, adjust the temperature to 50°C, keep warm, and stir for 30 minutes;
[0108] Lauryl acrylate, sodium dodecyl sulfate, castor oil and deionized water were mixed in sequence and stirred at high speed for 10 minutes to obtain a composite liquid;
[0109] adding the initiator to water to prepare an initiator solution;
[0110] The initiator solution was added to the composite solution and stirred for 10 min to obtain a mixed solution;
[0111] The mixed solution was added dropwise into the reaction kettle at a volume ratio of 1:3, the temperature was adjusted to 80° C., the mixture was stirred for 4 hours, and then cooled to room temperature to obtain a wetting agent.
[0112] The composite emulsifier is a mixture of alkylphenol polyoxyethylene ether and sodium lauryl sulfate;
[0113] The mixing mass ratio of the alkylphenol polyoxyethylene ether and sodium lauryl sulfate is 3:1.2;
[0114] The mass ratio of the composite emulsifier to deionized water is 1:28.
[0115] The mixing mass ratio of methyl methacrylate and isooctyl acrylate is 2:1;
[0116] The mass ratio of methyl methacrylate to composite emulsifier is 45:1;
[0117] The mixing mass ratio of the lauryl acrylate, sodium lauryl sulfate, castor oil and deionized water is 12:1:3:30.
[0118] The mass fraction of the initiator solution is 3%;
[0119] The initiator is ammonium persulfate;
[0120] The mixing mass ratio of the initiator solution to the composite solution is 1:40.
[0121] The preparation method of nano-silica aerogel is as follows:
[0122] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 15 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0123] Among them, the stirring speed is 500r / min;
[0124] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 55:6:2;
[0125] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2;
[0126] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 40° C., the mixture was stirred for 2 hours, and then silica sol was added, and the mixture was stirred for 20 minutes to obtain.
[0127] The mass ratio of deionized water and methyltriethoxysilane is 45:10;
[0128] The volume ratio of deionized water to silica sol is 10:1;
[0129] Among them, the heat preservation stirring speed is 250r / min.
[0130] The nano-silica aerogel glass fiber mat comprises 3 layers of glass fiber mat and 2 layers of nano-silica aerogel.
[0131] The preparation method of nano-silicon dioxide aerogel glass fiber felt comprises the following steps:
[0132] (1) Prepare the substrate: glass fiber mat;
[0133] (2) preparing nano-silicon dioxide aerogel;
[0134] (3) Coating:
[0135] The nano-silica aerogel is uniformly coated on the surface of the glass fiber mat, and then covered with another layer of glass fiber mat, and then a layer of nano-silica aerogel is repeatedly coated on the surface of the new glass fiber mat, and then covered with another layer of glass fiber mat to obtain a preliminary sample;
[0136] (4) Hot pressing curing:
[0137] The obtained preliminary sample was placed at a temperature of 62°C and hot pressed for 1 hour, wherein the hot pressing pressure was 0.12 MPa;
[0138] (5) Aging:
[0139] After hot pressing, the product is aged for 3 days in an air atmosphere at 55°C.
[0140] Example 3
[0141] Nano-silica aerogel glass fiber mat, wherein the nano-silica aerogel glass fiber mat is obtained by treating the glass fiber mat with a sizing agent and then laminating it with nano-silica aerogel;
[0142] Among them, the mixing ratio of glass fiber mat and sizing agent is 1:11;
[0143] The nano-silicon dioxide aerogel layer is formed by coating nano-silicon dioxide aerogel on the surface of glass fiber mat and then curing it.
[0144] The thickness of the glass fiber felt layer is 2 mm; the thickness of the nano-silica aerogel layer is 1 mm.
[0145] The preparation method of the infiltrant is:
[0146] Add deionized water and composite emulsifier into the reactor and stir and mix for 15 minutes;
[0147] Add methyl methacrylate and isooctyl acrylate into the reactor, adjust the temperature to 50°C, keep warm, and stir for 30 minutes;
[0148] Lauryl acrylate, sodium dodecyl sulfate, castor oil and deionized water were mixed in sequence and stirred at high speed for 10 minutes to obtain a composite liquid;
[0149] adding the initiator to water to prepare an initiator solution;
[0150] The initiator solution was added to the composite solution and stirred for 10 min to obtain a mixed solution;
[0151] The mixed solution was added dropwise into the reaction kettle at a volume ratio of 1:3, the temperature was adjusted to 80° C., the mixture was stirred for 4 hours, and then cooled to room temperature to obtain a wetting agent.
[0152] The composite emulsifier is a mixture of alkylphenol polyoxyethylene ether and sodium lauryl sulfate;
[0153] The mixing mass ratio of the alkylphenol polyoxyethylene ether and sodium lauryl sulfate is 3:1;
[0154] The mass ratio of the composite emulsifier to deionized water is 1:28.
[0155] The mixing mass ratio of methyl methacrylate and isooctyl acrylate is 2:1;
[0156] The mass ratio of methyl methacrylate to composite emulsifier is 42:1;
[0157] The mixing mass ratio of the lauryl acrylate, sodium lauryl sulfate, castor oil and deionized water is 11:1:3:30.
[0158] The mass fraction of the initiator solution is 3%;
[0159] The initiator is ammonium persulfate;
[0160] The mixing mass ratio of the initiator solution to the composite solution is 1:40.
[0161] The preparation method of nano-silica aerogel is as follows:
[0162] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 15 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0163] Among them, the stirring speed is 500r / min;
[0164] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 55:6:2;
[0165] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2;
[0166] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 40° C., the mixture was stirred for 2 hours, and then silica sol was added, and the mixture was stirred for 20 minutes to obtain.
[0167] The mass ratio of deionized water and methyltriethoxysilane is 45:10;
[0168] The volume ratio of deionized water to silica sol is 10:1;
[0169] Among them, the heat preservation stirring speed is 250r / min.
[0170] The nano-silica aerogel glass fiber mat comprises 3 layers of glass fiber mat layers and 2 layers of nano-silica aerogel layers.
[0171] The preparation method of nano-silicon dioxide aerogel glass fiber felt comprises the following steps:
[0172] (1) Prepare the substrate: glass fiber mat;
[0173] (2) preparing nano-silicon dioxide aerogel;
[0174] (3) Coating:
[0175] The nano-silicon dioxide aerogel is uniformly coated on the surface of the glass fiber mat, and then covered with another layer of glass fiber mat, and then a layer of nano-silicon dioxide aerogel is repeatedly coated on the surface of the new glass fiber mat, and then covered with another layer of glass fiber mat to obtain a preliminary sample;
[0176] (4) Hot pressing curing:
[0177] The obtained preliminary sample was placed at a temperature of 64°C and hot pressed for 1 hour, wherein the hot pressing pressure was 0.12 MPa;
[0178] (5) Aging:
[0179] After hot pressing, the product is aged for 3 days in an air atmosphere at 55°C.
[0180] Example 4
[0181] Nano-silica aerogel glass fiber mat, wherein the nano-silica aerogel glass fiber mat is obtained by treating the glass fiber mat with a sizing agent and then laminating it with nano-silica aerogel;
[0182] Among them, the mixing ratio of glass fiber mat and sizing agent is 1:11;
[0183] The nano-silicon dioxide aerogel layer is formed by coating nano-silicon dioxide aerogel on the surface of glass fiber mat and then curing it.
[0184] The thickness of the glass fiber felt layer is 2 mm; the thickness of the nano-silica aerogel layer is 1 mm.
[0185] The preparation method of the infiltrant is:
[0186] Add deionized water and composite emulsifier into the reactor and stir and mix for 15 minutes;
[0187] Add methyl methacrylate and isooctyl acrylate into the reactor, adjust the temperature to 50°C, keep warm, and stir for 30 minutes;
[0188] Lauryl acrylate, sodium dodecyl sulfate, castor oil and deionized water were mixed in sequence and stirred at high speed for 10 minutes to obtain a composite liquid;
[0189] adding the initiator to water to prepare an initiator solution;
[0190] The initiator solution was added to the composite solution and stirred for 10 min to obtain a mixed solution;
[0191] The mixed solution was added dropwise into the reaction kettle at a volume ratio of 1:3, the temperature was adjusted to 80° C., the mixture was stirred for 4 hours, and then cooled to room temperature to obtain a wetting agent.
[0192] The composite emulsifier is a mixture of alkylphenol polyoxyethylene ether and sodium lauryl sulfate;
[0193] The mixing mass ratio of the alkylphenol polyoxyethylene ether and sodium lauryl sulfate is 3:1.1;
[0194] The mass ratio of the composite emulsifier to deionized water is 1:28.
[0195] The mixing mass ratio of methyl methacrylate and isooctyl acrylate is 2:1;
[0196] The mass ratio of methyl methacrylate to composite emulsifier is 44:1;
[0197] The mixing mass ratio of the lauryl acrylate, sodium lauryl sulfate, castor oil and deionized water is 13:1:3:30.
[0198] The mass fraction of the initiator solution is 3%;
[0199] The initiator is ammonium persulfate;
[0200] The mixing mass ratio of the initiator solution to the composite solution is 1:40.
[0201] The preparation method of nano-silica aerogel is as follows:
[0202] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 15 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0203] Among them, the stirring speed is 500r / min;
[0204] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 55:6:2;
[0205] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2;
[0206] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 40° C., the mixture was stirred for 2 hours, and then silica sol was added, and the mixture was stirred for 20 minutes to obtain.
[0207] The mass ratio of deionized water and methyltriethoxysilane is 45:10;
[0208] The volume ratio of deionized water to silica sol is 10:1;
[0209] Among them, the heat preservation stirring speed is 250r / min.
[0210] The nano-silica aerogel glass fiber mat comprises 3 layers of glass fiber mat and 2 layers of nano-silica aerogel.
[0211] The preparation method of nano-silicon dioxide aerogel glass fiber felt comprises the following steps:
[0212] (1) Prepare the substrate: glass fiber mat;
[0213] (2) preparing nano-silicon dioxide aerogel;
[0214] (3) Coating:
[0215] The nano-silica aerogel is uniformly coated on the surface of the glass fiber mat, and then covered with another layer of glass fiber mat, and then a layer of nano-silica aerogel is repeatedly coated on the surface of the new glass fiber mat, and then covered with another layer of glass fiber mat to obtain a preliminary sample;
[0216] (4) Hot pressing curing:
[0217] The obtained preliminary sample was placed at a temperature of 62°C and hot pressed for 1 hour, wherein the hot pressing pressure was 0.12 MPa;
[0218] (5) Aging:
[0219] After hot pressing, the product is aged for 3 days in an air atmosphere at 55°C.
[0220] Example 5
[0221] Nano-silica aerogel glass fiber mat, wherein the nano-silica aerogel glass fiber mat is obtained by treating the glass fiber mat with a sizing agent and then laminating it with nano-silica aerogel;
[0222] Among them, the mixing ratio of glass fiber mat and sizing agent is 1:12;
[0223] The nano-silicon dioxide aerogel layer is formed by coating nano-silicon dioxide aerogel on the surface of glass fiber mat and then curing it.
[0224] The thickness of the glass fiber felt layer is 2 mm; the thickness of the nano-silica aerogel layer is 1 mm.
[0225] The preparation method of the infiltrant is:
[0226] Add deionized water and composite emulsifier into the reactor and stir and mix for 15 minutes;
[0227] Add methyl methacrylate and isooctyl acrylate into the reactor, adjust the temperature to 50°C, keep warm, and stir for 30 minutes;
[0228] Lauryl acrylate, sodium dodecyl sulfate, castor oil and deionized water were mixed in sequence and stirred at high speed for 10 minutes to obtain a composite liquid;
[0229] adding the initiator to water to prepare an initiator solution;
[0230] The initiator solution was added to the composite solution and stirred for 10 min to obtain a mixed solution;
[0231] The mixed solution was added dropwise into the reaction kettle at a volume ratio of 1:3, the temperature was adjusted to 80° C., the mixture was stirred for 4 hours, and then cooled to room temperature to obtain a wetting agent.
[0232] The composite emulsifier is a mixture of alkylphenol polyoxyethylene ether and sodium lauryl sulfate;
[0233] The mixing mass ratio of the alkylphenol polyoxyethylene ether and sodium lauryl sulfate is 3:1.2;
[0234] The mass ratio of the composite emulsifier to deionized water is 1:28.
[0235] The mixing mass ratio of methyl methacrylate and isooctyl acrylate is 2:1;
[0236] The mass ratio of methyl methacrylate to composite emulsifier is 45:1;
[0237] The mixing mass ratio of the lauryl acrylate, sodium lauryl sulfate, castor oil and deionized water is 14:1:3:30.
[0238] The mass fraction of the initiator solution is 3%;
[0239] The initiator is ammonium persulfate;
[0240] The mixing mass ratio of the initiator solution to the composite solution is 1:40.
[0241] The preparation method of nano-silica aerogel is as follows:
[0242] First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 15 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution;
[0243] Among them, the stirring speed is 500r / min;
[0244] The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 55:6:2;
[0245] The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2;
[0246] Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 40° C., the mixture was stirred for 2 hours, and then silica sol was added, and the mixture was stirred for 20 minutes to obtain.
[0247] The mass ratio of deionized water and methyltriethoxysilane is 45:10;
[0248] The volume ratio of deionized water to silica sol is 10:1;
[0249] Among them, the heat preservation stirring speed is 250r / min.
[0250] The nano-silica aerogel glass fiber mat comprises 3 layers of glass fiber mat layers and 2 layers of nano-silica aerogel layers.
[0251] The preparation method of nano-silicon dioxide aerogel glass fiber felt comprises the following steps:
[0252] (1) Prepare the substrate: glass fiber mat;
[0253] (2) preparing nano-silicon dioxide aerogel;
[0254] (3) Coating:
[0255] The nano-silicon dioxide aerogel is uniformly coated on the surface of the glass fiber mat, and then covered with another layer of glass fiber mat, and then a layer of nano-silicon dioxide aerogel is repeatedly coated on the surface of the new glass fiber mat, and then covered with another layer of glass fiber mat to obtain a preliminary sample;
[0256] (4) Hot pressing curing:
[0257] The obtained preliminary sample was placed at a temperature of 65°C and hot pressed for 1 hour, wherein the hot pressing pressure was 0.12 MPa;
[0258] (5) Aging:
[0259] After hot pressing, the product is aged for 3 days in an air atmosphere at 55°C.
[0260] Comparative Example 1:
[0261] Based on the technical solution of Example 1, no wetting treatment with a wetting agent is performed, and the rest of the technical solutions remain unchanged.
[0262] test:
[0263] The sound insulation performance of the samples of the embodiment and the comparative example was tested according to the GB / Z22764-2011 standard:
[0264] The test frequency is 4000Hz;
[0265] Ten samples were measured in each group and the average value was taken;
[0266] Table 1
[0267] Maximum sound insulation dB Example 1 16.32 Example 2 16.83 Example 3 16.57 Example 4 16.29 Example 5 16.78 Comparative Example 1 13.07
[0268] It can be seen from Table 1 that the nano-silica aerogel glass fiber felt prepared in the present invention has excellent sound insulation performance.
[0269] Taking Example 1 as the basic sample, the sound insulation performance under different frequencies was compared. Five samples were measured in each group in turn, and the average results were shown in Table 2:
[0270] Table 2
[0271] Frequency Hz Maximum sound insulation dB 500 10.24 1000 12.17 2000 14.36 3000 15.87 4000 16.32 5000 16.88 6000 17.25
[0272] It can be seen from Table 2 that with the increase of frequency, the maximum sound insulation of the nano-silica aerogel glass fiber felt prepared by the present invention continues to increase.
[0273] The water absorption rate of each group of the embodiment and the comparative example was tested:
[0274] Table 3
[0275]
[0276]
[0277] It can be seen from Table 3 that the water absorption rate of the nano-silica aerogel glass fiber felt prepared by the present invention is low and it is not easy to absorb water.
[0278] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.
Claims
1. Nano-silica aerogel glass fiber mat, characterized in that: The nano-silica aerogel glass fiber mat is obtained by treating the glass fiber mat with a sizing agent and then laminating it with the nano-silica aerogel; Among them, the mixing ratio of glass fiber mat and sizing agent is 1:10-12; The nano-silicon dioxide aerogel layer is formed by coating nano-silicon dioxide aerogel on the surface of glass fiber mat and then curing it.
2. The nano-silica aerogel glass fiber mat according to claim 1, characterized in that: The thickness of the glass fiber felt layer is 0.2-0.3 mm; the thickness of the nano silicon dioxide aerogel layer is 0.1-0.2 mm.
3. The nano-silica aerogel glass fiber mat according to claim 1, characterized in that: The preparation method of the infiltrant is as follows: Add deionized water and composite emulsifier into the reactor and stir and mix for 15 minutes; Add methyl methacrylate and isooctyl acrylate into the reactor, adjust the temperature to 50°C, keep warm, and stir for 30 minutes; Lauryl acrylate, sodium dodecyl sulfate, castor oil and deionized water were mixed in sequence and stirred at high speed for 10 minutes to obtain a composite liquid; adding the initiator to water to prepare an initiator solution; The initiator solution was added to the composite solution and stirred for 10 min to obtain a mixed solution; The mixed solution was added dropwise into the reaction kettle at a volume ratio of 1:3, the temperature was adjusted to 80° C., the mixture was stirred for 4 hours, and then cooled to room temperature to obtain a wetting agent.
4. The nano-silica aerogel glass fiber mat according to claim 3, characterized in that: The composite emulsifier is a mixture of alkylphenol polyoxyethylene ether and sodium lauryl sulfate; The mixing mass ratio of the alkylphenol polyoxyethylene ether and sodium lauryl sulfate is 3:1-1.2; The mass ratio of the composite emulsifier to deionized water is 1:
28.
5. The nano-silica aerogel glass fiber mat according to claim 3, characterized in that: The mixing mass ratio of methyl methacrylate and isooctyl acrylate is 2:1; The mass ratio of methyl methacrylate to composite emulsifier is 42-45:1; The mixing mass ratio of the lauryl acrylate, sodium lauryl sulfate, castor oil and deionized water is 10-14:1:3:
30.
6. The nano-silica aerogel glass fiber mat according to claim 5, characterized in that: The mass fraction of the initiator solution is 3%; The initiator is ammonium persulfate; The mixing mass ratio of the initiator solution to the composite liquid is 1:
40.
7. The nano-silica aerogel glass fiber mat according to claim 1, characterized in that: The nano silicon dioxide aerogel preparation method is: First, deionized water, acetic acid and hexadecyltrimethylammonium bromide were added into a reaction kettle, stirred for 15 minutes, and then ultrasonically dispersed for 10 minutes to obtain a mixed solution; Among them, the stirring speed is 500r / min; The mass ratio of deionized water, acetic acid and hexadecyltrimethylammonium bromide is 55:6:2; The molar ratio of methyltriethoxysilane to diethoxydimethylsilane is 1:2; Methyltriethoxysilane and diethoxydimethylsilane were added to the mixed solution in sequence, the temperature was adjusted to 40° C., the mixture was stirred for 2 hours, and then silica sol was added, and the mixture was stirred for 20 minutes to obtain.
8. The nano-silica aerogel glass fiber mat according to claim 6, characterized in that: The mixing mass ratio of the deionized water and methyltriethoxysilane is 45:10; The volume ratio of deionized water to silica sol is 10:1; Among them, the heat preservation stirring speed is 250r / min.
9. The nano-silica aerogel glass fiber mat according to claim 5, characterized in that: The nano-silica aerogel glass fiber mat comprises at least three glass fiber mat layers and at least two nano-silica aerogel layers.
10. The method for preparing the nano-silica aerogel glass fiber mat according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Prepare the substrate: glass fiber mat; (2) preparing nano-silicon dioxide aerogel; (3) Coating: The nano-silicon dioxide aerogel is uniformly coated on the surface of the glass fiber mat, and then covered with another layer of glass fiber mat, and then a layer of nano-silicon dioxide aerogel is repeatedly coated on the surface of the new glass fiber mat, and then covered with another layer of glass fiber mat to obtain a preliminary sample; (4) Hot pressing curing: The obtained preliminary sample was placed at a temperature of 60-65°C and hot pressed for 1 hour, wherein the hot pressing pressure was 0.12MPa; (5) Aging: After hot pressing, the product is aged for 3 days in an air atmosphere at 55°C.
Citation Information
Patent Citations
Glass fiber infiltration agent composition
CN101186450A
Process of binary component high-silica glass fiber wetting agent
CN102992649A
Bicomponent high silica glass fiber sizing agent
CN102992650A
Glass fiber infiltrating agent composition as well as preparation method and application thereof
CN103570255A
Carbon-nanotube-containing glass fiber wetting agent, and preparation method and application thereof
CN104086094A